Investigating the relationship between school attendance and academic performance in universal primary education: The case of Uganda - Sekiwu, Denis; Ssempala, Frederick; Naluwemba, Frances (African Educational Research Journal, 2020)
This study investigated the relationship between school attendance and academic performance in UPE schools in Rubanda district of Uganda. Using data from a sample of 104 participants, the researchers established that UPE schools perform poorer in internal examinations but better in national examinations. The regular school attendees perform differently from the chronic absentees. There is also a positive relationship between school attendance and academic performance (R = 0.365), although school attendance explains only 11.8% variations in academic performance while 88.2% is explained by other factors affecting academic performance. School administrators should identify other factors that are likely to influence pupils' academic performance apart from attendance, as well as strengthening communityschool interaction programmes to help improve attendance in UPE schools.
Keywords: Academic performance; School attendance; UPE schools; Social productivity